Association of parents' alcohol use and family interaction with the initiation of alcohol use by sixth graders: A preliminary study in Taiwan - Hung Chao-Chia; Yen Lee-Lan; Wu Wen-Chi (BMC, 2009)
Abstract Background The family is the main environment where children are socialized and learn individual behavior. Although previous studies have examined predictors of preadolescent first alcohol use, few studies have analyzed factors associated with alcohol use in children in a country with low alcohol consumption. The aim of this study was to investigate the initiation of alcohol use by sixth graders and determine family factors associated with first alcohol use. Methods Data used in this study was collected as part of the Child and Adolescent Behaviors in Long-term Evolution (CABLE) project in 2002 (when study participants were in grade 5 and aged 10-11 years) and 2003 (when study participants were in grade 6 and aged 11-12 years). Data from a total of 1,183 participants was analyzed. Main study variables included children's alcohol use: (1) never user (never user in 2002 and 2003), or (2) first-time user (never user in 2002 but ever user in 2003); parents' alcohol use: (1) both parents ever users, (2) mother ever user and father never user, (3) father ever user and mother never user, (4) both parents never users; parental support; and family conflict. Correlates of first alcohol use were identified using logistic regression. Results There were 183 students (15.5%) who became first-time users of alcohol in the sixth grade. Having parents who both used alcohol, less parental support, and more family conflict were significant predictors of sixth graders' first alcohol use. Family interaction and parents' drinking were equally important predictors of preteen's first use of alcohol. Conclusion Family factors influence children's initiation of alcohol use. It is important to educate parents about the effects of alcohol on children and to emphasize the importance of prevention.